2018
DOI: 10.1136/bmjoq-2017-000066
|View full text |Cite
|
Sign up to set email alerts
|

A quality improvement project aimed at adapting primary care to ensure the delivery of evidence-based psychotherapy for adult anxiety

Abstract: Primary care patients frequently present with anxiety with prevalence ratios up to 30%. Brief cognitive–behavioural therapy (CBT) has been shown in meta-analytic studies to have a strong effect size in the treatment of anxiety. However, in surveys of anxious primary care patients, nearly 80% indicated that they had not received CBT. In 2010, a model of CBT (Coordinated Anxiety Learning and Management (CALM)) adapted to primary care for adult anxiety was published based on results of a randomised controlled tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
(21 reference statements)
1
8
0
Order By: Relevance
“…In this study, the treatment response rate for the GAD-7 was 45% (13/29). The response rates of PHQ-9 and GAD-7 in this study were similar to those in a prior study [89]. Taken together, our results suggest that videoconference-delivered CBT for OCD, PD, and SAD might secondarily ameliorate symptoms for generalized anxiety and depression.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, the treatment response rate for the GAD-7 was 45% (13/29). The response rates of PHQ-9 and GAD-7 in this study were similar to those in a prior study [89]. Taken together, our results suggest that videoconference-delivered CBT for OCD, PD, and SAD might secondarily ameliorate symptoms for generalized anxiety and depression.…”
Section: Discussionsupporting
confidence: 87%
“…There were significant differences in changes between the OCD and PD groups (OCD: P =.002; PD: P =.006; SAD: P =.10) at week 16. A previous study reported a response rate in GAD-7 of 50.9% following a computerized CBT program, for 1062 adults who had GAD-7 scores of 10 or more at baseline [89] including 75 patients with GAD, 47 with PD, 40 with SAD, and 18 with PTSD. In this study, the treatment response rate for the GAD-7 was 45% (13/29).…”
Section: Discussionmentioning
confidence: 99%
“…Several methodological approaches were identified to generate data from existing programs : naturalistic, open, or "phase 4" studies [ 11 , 44 , 45 , 62 , 70 72 ], observational studies from routine care [ 73 ], implementation or program evaluation studies [ 49 , 74 78 ], and quality improvement research [ 79 ]. While the degree of overlap between these methodologies is beyond this review’s scope, their variety in published studies highlights the recognized importance of learning from existing programs.…”
Section: Resultsmentioning
confidence: 99%
“…Documents analyzed included reports on existing programs aiming to improve access to CBT for anxiety disorders through treatment modalities such as telephone CBT [ 74 ], internet-delivered CBT [ 70 73 , 75 , 77 , 78 ], and transdiagnostic group CBT. Some studies reported on an implemented training program [ 76 ], an approach to collaborative care [ 79 ], or CBT practices in primary care settings [ 44 ]. Other existing programs had the broader aim of improving access to various mental health services (including CBT) through a national-level endeavor [ 81 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation